2018
DOI: 10.7824/rbh.v17i1.538
|View full text |Cite
|
Sign up to set email alerts
|

Modelagem matemática do fluxo de emergência de plantas daninhas: ferramenta para decisão no manejo de cultivos

Abstract: Resumo -O surgimento de biótipos de plantas daninhas resistentes a herbicida e o aumento da pressão social para reduzir sua utilização, criou a necessidade de desenvolver ferramentas para aperfeiçoar a aplicação de herbicidas e melhorar o controle de plantas daninhas. Desta forma, o desenvolvimento de modelos de emergência de plantas daninhas tornou-se crucial para o desenvolvimento de estratégias de gerenciamento em áreas agrícolas. Esta revisão tem por objetivo apresentar os fatores que influenciam o fluxo d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…The knowledge about the germination aspects of plants at different times of the year allows for adapting management practices (Zandoná et al 2018a), enabling the effective use of herbicides and integrated weed management practices. To obtain effectiveness in integrated weed management, practices focused on weed seeds and aspects of the seed bank should be considered; i.e., crop rotations, soil tillage, and harvest weed seed control (Haring and Flessner 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The knowledge about the germination aspects of plants at different times of the year allows for adapting management practices (Zandoná et al 2018a), enabling the effective use of herbicides and integrated weed management practices. To obtain effectiveness in integrated weed management, practices focused on weed seeds and aspects of the seed bank should be considered; i.e., crop rotations, soil tillage, and harvest weed seed control (Haring and Flessner 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Several authors, such as Buhler et al (1995), Vidal and Bauman (1996), Pereira et al (2012), andZandoná et al (2018), showed how the survival of species considered weeds may be related to non-germination of seeds in unfavorable environmental conditions, characterizing ecological significance, as it prevents the development of seedlings in soils without sufficient resources to support subsequent growth. Thus, species whose seeds do not have this control mechanism could all germinate at the same time, after a short period of soil wetting, compromising the development of formed individuals and future generations (Van Den Berg & Zeng, 2006;Pereira et al, 2012).…”
mentioning
confidence: 99%